1992
DOI: 10.1143/jjap.31.1258
|View full text |Cite
|
Sign up to set email alerts
|

Hole Compensation Mechanism of P-Type GaN Films

Abstract: Low-resistivity p-type GaN films, which were obtained by N2-ambient thermal annealing or low-energy electron-beam irradiation (LEEBI) treatment, showed a resistivity as high as 1×106 Ω·cm after NH3-ambient thermal annealing at temperatures above 600°C. In the case of N2-ambient thermal annealing at temperatures between room temperature and 1000°C, the low-resistivity p-type GaN films showed no change in resistivity, which was almost constant between 2 Ω·cm and 8 Ω·cm. These results indicate that atomic hydroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
497
2
26

Year Published

1998
1998
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 1,027 publications
(544 citation statements)
references
References 27 publications
19
497
2
26
Order By: Relevance
“…8 The predicted frequencies are 3100 cm -1 for V Ga -H and 3470 cm -1 for V Ga -H 4 and are close to the vibrational frequencies we have measured. Van de Walle also predicted a frequency of 600 cm -1 for the V N -H complex, 8 much lower than the vibrational frequencies we have seen.…”
Section: Vibrational Spectroscopysupporting
confidence: 83%
See 1 more Smart Citation
“…8 The predicted frequencies are 3100 cm -1 for V Ga -H and 3470 cm -1 for V Ga -H 4 and are close to the vibrational frequencies we have measured. Van de Walle also predicted a frequency of 600 cm -1 for the V N -H complex, 8 much lower than the vibrational frequencies we have seen.…”
Section: Vibrational Spectroscopysupporting
confidence: 83%
“…[1][2][3] These successes have depended, in part, on an improved understanding and control of defect processes such as the hydrogen passivation of acceptors in the nitrides. [4][5][6][7] Of particular interest here are recent studies of the interaction of hydrogen with native defects 8 and experimental results for the defects introduced in GaN by high-energy electron irradiation. 9,10 In this paper we report results for the defects introduced by the implantation of hydrogen into GaN.…”
Section: Introductionmentioning
confidence: 99%
“…In real experiments, the H2 pressure may be higher because of the unavoidable passivation of bulk or interface defects. The extra incorporation of H can be thermally annealed later [61] . Therefore, our results give a lower limit of H2 pressure.…”
Section: Table IImentioning
confidence: 99%
“…(1) it is more flexible to passivate different surfaces of various materials and satisfy ECR; (2) those hydrogen atoms diffused into bulk may passivate dangling bonds in the bulk or on the interfaces and improve the crystal quality by suppressing the formation of certain deep defects [49,59,60]; (3) H can be easily driven out by post-annealing treatment [61].…”
Section: Introductionmentioning
confidence: 99%
“…Especially the studies of hydrogen in metal oxides have been reported for various applications, [1][2][3][4][5] but hydrogen in metal nitrides has not been studied so much. As well as hydrogen in metal oxides, hydrogen in metal nitrides is very important when high quality p-type GaN thin films were prepared because hydrogen in p-type GaN plays a role of passivator against acceptor Mg. 6) Therefore it is so valuable to make the relationship clear between hydrogen and defects or impurities in the metal nitride thin films.…”
Section: Introductionmentioning
confidence: 99%